Effect of 12 weeks of resistance exercise on post-exercise hypotension in stage 1 hypertensive individuals - Moraes, M. R.; Bacurau, R. F.P.; Simões, H. G.; Campbell, C. S.G.; Pudo, M. A.; Wasinski, F.; Pesquero, J. B.; Würtele, M.; Araujo, R. C. (Springer Nature, 2012)
Post-exercise hypotension (PEH), the reduction of blood pressure (BP) after a single bout of exercise, is of great clinical relevance. As the magnitude of this phenomenon seems to be dependent on pre-exercise BP values and chronic exercise training in hypertensive individuals leads to BP reduction; PEH could be attenuated in this context. Therefore, the aim of the present study was to investigate whether PEH remains constant after resistance exercise training. Fifteen hypertensive individuals (46 ± 8 years; 88 ± 16 kg; 30 ± 6% body fat; 150 ± 13/93 ± 5 mm Hg systolic/diastolic BP, SBP/DBP) were withdrawn from medication and performed 12 weeks of moderate-intensity resistance training. Parameters of cardiovascular function were evaluated before and after the training period. Before the training program, hypertensive volunteers showed significant PEH. After an acute moderate-intensity resistance exercise session with three sets of 12 repetitions (60% of one repetition maximum) and a total of seven exercises, BP was reduced post-exercise (45-60 min) by an average of aproximately -22 mm Hg for SBP, -8 mm Hg for DBP and -13 mm Hg for mean arterial pressure (P < 0.05). However, this acute hypotensive effect did not occur after the 12 weeks of training (P > 0.05). In conclusion, our data demonstrate that PEH, following an acute exercise session, can indeed be attenuated after 12 weeks of training in hypertensive stage 1 patients not using antihypertensive medication. © 2012 Macmillan Publishers Limited All rights reserved.
Keywords: blood pressure; post-exercise hypotension; strength exercise